Modelling of Volatility at Czech Financial Markets - Trešl, Jiří (Modelowanie zmienności na czeskich rynkach finansowych, 2009)
At present, two principal approaches to volatility modelling exist: the GARCH and stochastic volatility models. In this paper, the GARCH models have been applied both to selected Czech capital market and exchange rates time series. The first aim of investigation consists in possible differences in behaviour with respect to time scale (days, weeks, months). The second level is given by differences between stock prices and exchange rates. Finally, besides univariate models, multivariate GARCH were also used to discover possible relations among different time series.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 72-82